Amalan Penjarakan Fizikal Dalam Solat Berjemaah Di Masjid Menurut Perspektif Maqasid Syariah - Nur Kamilah Kamaruddin; Siti Nor Azimah Sabaruddin; Nik Nurul Akmal Ab Alim; Tengku Maaidah Tengku A Razak; Mohd Ridhuwan Bin Remly; Nor Azrina @ Nor Azura Ab. Rahman (USIM Press, 2024)
Vol. 26 No. 2 (2021): Special Edition